ANALISIS PENDAPATAN SUPIR ANGKUTAN UMUM SEBELUM DAN DIMASA PANDEMI COVID-19 DITINJAU DARI PERSFEKTIF EKONOMI ISLAM (Studi Kasus Supir Angkutan Umum Di Kecamatan Panyabungan Kabupaten Mandailing Natal) - Mutiah Salsabila; Nurbaiti; Mawaddah Irham (EKSYA : Jurnal Ekonomi Syariah, 2022)
The income of public transport drivers is included in the Ujrah (Reward) method. This study aims to determine the income of public transport drivers before and during the Covid-19 pandemic and to determine the income of public transport drivers before and during the pandemic in terms of an Islamic economic perspective. The research method used is a qualitative method. Data collection techniques with the method of observation, interviews and documentation. The results of this study concluded that the income of public transport drivers during the Covid-19 pandemic in Panyabungan District decreased from before due to a decrease in the number of passengers due to government policies such as social distancing, lockdown, school holidays, offices and also calls to minimize leaving the house during the pandemic. Covid-19. The income of public transportation drivers in Panyabungan District before and during the Covid-19 pandemic in terms of the Islamic economic perspective is included in the Ujrah method because public transportation provides services to other people in need and then gets ujrah in the form of rental fees or paid for using these services. The decline in the income of public transport drivers in the District during the Covid-19 pandemic from before could threaten a person's monotheism because poverty can bring it closer to kufr, therefore public transport drivers must continue to work and always be grateful to Allah and do not forget to try to increase income from other things. of course income in accordance with Islamic law itself.